The Influence of Problem Based Learning Model on Increasing Self-Esteem and Learning Outcomes of Students on Excretory System Material - Laila, Nazila Nur; Kurniati, Tuti; Yusup, Iwan Ridwan (Sean Institute, 2024)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model on increasing Self-Esteem and student learning outcomes in the excretory system material. In this study, there are two types of variables used. First, the independent variable is the level of student self-esteem, and the dependent variable is the learning outcomes of students. The study was conducted at MTS Al-Misbah located at Jalan Desa Cipadung No.22, Cibiru District, Bandung City, West Java. The population in this study were all students of class VIII MTS Al-Misbah consisting of two classes, namely class VIII A and VIII B with a total of 73 students. The sampling method used was purposive sampling. The learning outcomes of students using the PBL model produced an N-gain of 0.7 with a high category. In addition, the results of self-esteem after using the PBL model got a high category, this proves that the learning model can affect the level of student self-esteem. The application of PBL in an effort to improve students' self-esteem is one solution where with this model students are more involved in the learning process so that it can improve students' self-esteem and learning outcomes. So, from the two hypothesis tests it can be concluded that there is an influence of the PBL learning model on improving students' Self-Esteem and learning outcomes in the excretory system material.